Protection of Performers’ Rights in Indonesian Copyright Law: Copyrighted Works Uploaded to YouTube - Yulia Yulia; Zinatul Ashiqin Zainol; Fatahillah F (Sriwijaya Law Review, 2023)
The Beijing Treaty allows performers to benefit from using audiovisual fixation for commercial purposes. This treaty is the first treaty specifically to protect against the head of the show. Indonesia has ratified the Beijing Treaty in order to give protection to the performers. There are provisions that performers can maintain moral rights until death (but not after death) and until the end of economic rights and refuse all forms of distortion, excision and modification that damage the reputation of performers. This article analyses the protection of the rights of performers whose works were uploaded without permission to YouTube under Indonesian Copyright Law 2014. This research is normative juridical research with a conceptual and statutory approach. The result is that the show performers’ performance rights under the Beijing Agreement have been adopted in the 2014 Indonesian Copyright Act, even though there are some differences in defining the fixation and scope of the show rights to the fixed performance terms. The 2014 Indonesian Copyright Law has indefinitely maximised the protection of performers' moral rights. Moreover, the Indonesian Copyright Law 2014 Act No. 28 states that the rights of performers cannot be eliminated or cannot be removed for any reason, including their economic rights, such as a  right to carry out themselves, give permission, prohibit broadcast or communication the performance to other parties, come under by using online media. Therefore, when an illegal act such as uploading the performance of performers without permission violates Copyright Law, dan perpetrators can be sued.